2022
DOI: 10.1024/0300-9831/a000676
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D can be effective on the prevention of COVID-19 complications: A narrative review on molecular aspects

Abstract: Abstract. The widespread COVID-19 pandemic has been, currently, converted to a catastrophic human health challenge. Vitamin D (VD) and its metabolites have been used as a palliative treatment for chronic inflammatory and infectious diseases from ancient times. In the current study, some molecular aspects of the potential effects of VD against COVID-19 side-effects have been discussed. An arguable role in autophagy or apoptosis control has been suggested for VD through calcium signaling at the mitochondrial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 108 publications
0
12
0
1
Order By: Relevance
“…Several viruses including coronavirus that cause a biochemical imbalance in the infected cell resulting in oxidative stress, which may be associated with the development of pathologies and worsening of symptoms 30,31 . Thus, the lower SOD level may indicate a worse prognosis, and antioxidants should be considered as a candidate therapeutic approach against SARS‐CoV‐2 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…Several viruses including coronavirus that cause a biochemical imbalance in the infected cell resulting in oxidative stress, which may be associated with the development of pathologies and worsening of symptoms 30,31 . Thus, the lower SOD level may indicate a worse prognosis, and antioxidants should be considered as a candidate therapeutic approach against SARS‐CoV‐2 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…Some vitamins are indicated to be effective in strengthening the immune system [ 2 , 24 ]. During the COVID-19 pandemic, the fact that these vitamins contribute to both protection from disease and the healing process in case of illness has mentioned in many publications [12] , [13] , [14] , [15] , [16] , [17] has been frequently emphasized in the media. Accordingly, in the study, a comparative search was conducted to determine the tendency for vitamins that have positive effects on strengthening the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…While vitamins C and E strengthen the immune system thanks to their high anti-inflammatory and antioxidant effect [ 10 , 11 ], it has been reported that vitamin D has an effect that can disrupt viral cellular infection by interacting with angiotensin converting enzyme (ACE) [11] . It is thought that vitamin D and vitamin C play an important role in determining the results of COVID-19 in many studies conducted to determine the efficacy of vitamins in the prognosis of COVID-19 [12] , [13] , [14] , [15] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%
“…A relationship between VD status and the incidence or the severity of respiratory infections in children has been found in many observational studies, and a recent review seems to support the protective role of VD against tuberculosis, otitis media, pharyngotonsillitis, bronchiolitis, and viral wheezing [ 5 , 6 , 7 ]. Even during the recent COVID-19 pandemic, VD and its metabolites were found to be useful both in inducing the antiviral response and in negatively regulating the renin-angiotensin-aldosterone system, including the expression of ACE2, the receptor for SARS-CoV2 [ 8 , 9 ]. The influence of VD status on the clinical outcome of patients with COVID-19 is still undefined, as studies have shown conflicting results [ 10 , 11 , 12 ].…”
Section: Vitamin Dmentioning
confidence: 99%